Analysis Of The Quality Performance of the Very Small Aperture Terminal Internet Network at the Darussyahidin Nw Langko Islamic Boarding School - Ardi Rahmawan; A. Haris; Faridatun Sholehah; Puji Laila Ramadhan (Lembaga Penelitian dan Pendidikan Mandala, 2026)
The development of information technology has brought significant changes to human life, particularly through internet services that facilitate access to information and communication. The need for quality internet services is increasing, including in the education sector. However, not all regions in Indonesia have equal access to the internet, particularly remote areas with limited network infrastructure. One example is the Darussyahidin NW Langko Islamic Boarding School, which experiences difficulties in accessing conventional internet services. To overcome this obstacle, in 2019 the Islamic boarding school adopted VSAT (Very Small Aperture Terminal) satellite technology as a solution to provide internet access for students and teachers. However, an evaluation of the quality of the resulting internet service is necessary to optimally support the learning process. This study aims to analyze the quality of VSAT network services at the Darussyahidin NW Langko Islamic Boarding School. The analysis was conducted by considering Quality of Service (QoS) parameters such as delay, jitter, packet loss, and throughput. This study also compares the results with several previous studies that discussed VSAT network performance in various contexts. The research results are expected to provide an overview of the quality of VSAT internet services in supporting learning activities, as well as being a reference in developing and improving network services in remote areas.